Mangrove forest structure, water quality, and carbon storage at Palmares, northern Pacific coast of Costa Rica - Samper-Villarreal, Jimena (2026)
Introduction: Mangroves provide many ecosystem services, yet they continue to be degraded and decline in numbers. Effective management strategies need baseline information to assess habitat condition and potential decline. In Costa Rica, mangroves on the North Pacific are the least studied. Objective: To provide the first characterization of forest structure and carbon content of the Palmares mangrove. Methods: A total of 58 square plots (5 × 5 m) were sampled between March 2022 and April 2023. In each plot, mangrove species, stem height, and circumference were quantified. Samples were collected to estimate interstitial water salinity, fine root content, and sediment grain size, bulk density, and carbon content. Mangrove biomass and organic carbon (OC) were calculated using allometric equations. Water quality was assessed at six sites in the main channel during the dry and rainy seasons of 2023. Results: Six mangrove species were identified at Palmares. Rhizophora spp. (55 % of plots) and Avicennia spp. (29 %) were the most abundant, while Laguncularia and Conocarpus were rare. Average tree height was 8 ± 7 m, width 11 ± 12 cm, and density 1 833 ± 1 757 stems ha-1. Rhizophora spp. were taller and wider than Avicennia spp. Interstitial water salinity at Palmares was 34 ± 14, which was higher during the dry season and in Avicennia spp. plots. Sediment was mainly composed of silt-clay (52 %), which was higher in Rhizophora spp. plots. Sediment bulk density was 0.8 ± 0.3 g cm-3 and fine roots < 1 %. Above-ground biomass OC averaged 224 ± 335 Mg ha-1 and was higher in Rhizophora spp. plots. Sediment OC was 8 ± 3 % and inorganic carbon 3 ± 1 %. OC was higher in sediments of Rhizophora spp., with higher silt-clay, larger mangroves, and lower densities. There was no clear pattern of variation in water parameters along the main channel. Conclusions: This first characterization of Palmares mangrove can serve as a baseline for further studies and effective management and conservation strategies.